2016
DOI: 10.1007/s11547-016-0695-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced sarcomas of the head and neck in post-radiation nasopharyngeal carcinoma

Abstract: common, with a crude incidence in adults of less than 0.5 % in various situations [1][2][3][4][5]. With improved patient survival [6][7][8], RIS is likely to be encountered more frequently. It is now generally believed that complete surgical resection of RIS provides the only chance of a cure [3,4]. Unfortunately, the reported prognosis is poor owing to advanced RIS at diagnosis [3,4,9]. RIS has become a critical problem that can limit long-term survival and hinder quality of life. To detect an RIS at an earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
16
0
1
Order By: Relevance
“…In previous studies, researchers have observed that this lesion in the head and neck is mainly found in the fifth decade of life. 7,10,19 We found a mean age of 50 years old, with a higher age among males than females. The tumors also showed a male predilection, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In previous studies, researchers have observed that this lesion in the head and neck is mainly found in the fifth decade of life. 7,10,19 We found a mean age of 50 years old, with a higher age among males than females. The tumors also showed a male predilection, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 72%
“…The tumors also showed a male predilection, consistent with previous studies. 7,10 RISOC primary lesions most commonly affected the nasopharynx and tongue. 4,5,10,20 These entities demonstrated a mean time to diagnosis of 2.4 months and a mean tumor size of 2.6 cm, consistent with previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of radiation-induced sarcoma (RIS) ranges from 0.03 to 0.3% and the most common location was the maxillary region, including the maxillary sinus, alveolar process, palate, and adjacent nasal cavity [2,4] RIS developed within the radiation volume for the primary tumour in which the mean radiation dose for the primary tumour was 33 Gy (range: 25-50Gy); the mean latency period between radiation therapy and occurrence of the sarcoma was 15 years (range of 3-50 years) [5] For bone sarcomas Cahan et al has developed the first set criteria for RIS [6] Murray et al revised these to include other soft tissue sarcomas [7] These criteria was further modified as such: (i) a prior history of radiation; (ii) development of a sarcoma in the field of radiation; (iii) a latency period of at least 2 years between radiation and appearance of the sarcoma and (iv) evidence that the sarcoma is histologically different from the irradiated primary cancer [8] The average latency period from the time-of-radiation to the time-of-diagnosis of the RIS was 12.6 years (range of 3-30 years) and it was believed that squamous cell carcinoma will be presented at a mean duration of 12.5 years post radiation. Sarcomas will be presented a bit sooner, around 8.8 years post radiation.…”
Section: Discussionmentioning
confidence: 99%